Korupsi Ditinjau dari Kitab Amsal - Silalahi, Bonnarty Steven (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
This study explores the perspective of the Book of Proverbs on corruption, focusing on how its teachings can be applied to combat corruption in the modern context. The moral and spiritual dimensions of corruption are often overlooked in modern legal approaches, whereas the Book of Proverbs provides profound insights into corruption as a manifestation of the human heart's depravity. This study employs a topical method, analyzing ten selected verses from the Book of Proverbs in their original Hebrew and modern translations. The findings reveal that the Book of Proverbs consistently opposes corrupt practices such as fraud, bribery, and oppression, offering solutions grounded in moral and spiritual transformation through Christian values. By establishing integrity, justice, and faithfulness to God as moral foundations, the teachings of Proverbs provide relevant guidance for shaping individual behavior and equitable leadership in modern society. This study concludes that the teachings of the Book of Proverbs offer a Christian-based framework for building a corruption-free society and upholding justice.